Equal Pro-inflammatory Profiles of CCLs, CXCLs, and Matrix Metalloproteinases in the Extracellular Microenvironment In Vivo in Human Dense Breast Tissue and Breast Cancer - Abrahamsson, Annelie; Rzepecka, Anna; Dabrosin, Charlotta (Frontiers in Immunology, 2018)
The inflammatory microenvironment affects breast cancer progression. Proteins that govern the inflammatory response are secreted into the extracellular space, but this compartment still needs to be characterized in human breast tissues in vivo. Dense breast tissue is a major risk factor for breast cancer by yet unknown mechanisms and no non-toxic prevention for these patients exists. Here, we used the minimal invasive technique of microdialysis for sampling of extracellular proteins in live tissues in situ in breast cancers of women before surgery and in healthy women having dense or nondense breast tissue on mammography. Proteins were profiled using a proximity extension assay. Out of the 32 proteins assessed, 26 exhibited similar profiles in breast cancers and dense breast tissues; CCL-4, -7, -8, -11, -15, -16, -22, -23, and -25, CXCL-5, -8, -9, -16 as well as sIL-6R, IL-18, VEGF, TGF-α, FGF-19, MMP-1, -2, -3, and uPA were all increased whereas CCL-3, CX3CL-1, HGF, and MMP-9 were unaltered in the two tissues. CCL-19 and -24, CXCL-1 and-10, and IL-6 were increased in dense breast tissue only whereas IL-18BP was increased in breast cancer only. Our results provide novel insights in the inflammatory microenvironment in human breast cancer in situ and define potential novel therapeutic targets. Additionally, we show previously unrecognized similarities of the pro-inflammatory microenvironment in dense breast tissue and breast cancer in vivo suggesting that anti-inflammatory breast cancer prevention trials for women with dense breast tissue may be feasible.